Poetics of the Performative in Translation – Ryszard Wojnakowski as the Translator of Friederike Mayröcker’s Poetry - Sommerfeld, Beate (Porównania, 2020)
The article discusses some Polish translations of the lyrical texts of the Austrian poetress Friederike Mayröcker by Ryszard Wojnakowski in the perspective of the theory of the performative – in its initial version by J. L. Austin and in its poststructuralist revisions. It depicts the performative nature of Mayröcker’s poetry which consists in the theatralization of texts, ritualized speech acts that have an auto-reference character and iteration mechanisms. Translation is seen as a re-staging and re-citation of the meanings of the original. Translation is understood as a creative activity that emphasizes the role of the translator, whereas the performative view counteracts the “invisibility” of the translator (Venuti).